Kinerja, Kesejahteraan Psikologis dan Nature Relatedness Pada Penenun Warna Alam di Kabupaten Sikka Provinsi NTT - Viktor Eko Transilvanus; Maria Megaloma Harten Gaharpung (Universitas Nusa Nipa Maumere, 2025)
This study aims to determine the role of Psychological Well-being as a mediator of Nature Related (NR) with Performance in natural dye weavers. Data collection using the modified NR scale from Adiwena & Djuwita, the modified Psychological Well-being Scale from Ryff & Keyes (1995) and the Performance Scale from Ramos-Villagrasa et al. (2019) on 157 natural dye weavers. Data analysis using regression with mediators. The results of the study show that Psychological Well-being can mediate NR and Performance (P-Value = 0.05) with an influence value of 0.141. The mediating role of Psychological Well-being complements previous studies that show the relationship between Nature Related, Psychological Well-being and Performance but have not placed Psychological Well-being as a mediator, especially in the context of non-formal work such as natural dye weavers.